Quest in Models from the Poetry of the Pre-Islamic Knights (Technical Study) - حدّاد , مصطفى حسن; معلاّ, مارلين منير (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research seeks to clarify the aspirations of the knightly poets in the pre-Islamic era and to identify the methods they used in achieving their goal. Thus, it investigates some of the repetitive patterns in their poetry.. The research has chosen to examine samples of the poetry of Antara al-Absi, Hatim al-Ta'i, and Amer Ibn al-Tafil. The first one suffered to extract his freedom and prove himself. He revealed the whiteness of actions and the good qualities hidden behind his black mantle, so he fixed them in his poetry to be realized by everyone who denied them and blamed him for the blackness of his skin. The second one was the master of generosity who took for himself a doctrine of generosity and altruism and mortgaged his life for that. As for Amer, he was the master of his people and their brave knight, who sought to immortalize his memory of heroism and good manners.. After study and analysis, the research found out that the recurring patterns in their poetry are many, including: their raise from every vile act and their unbridled pursuit of sublime. Likewise, they are trying to achieve the ideal heroic human model to reach some kind of immortality.